Luciferin detection after intra-nasal vector delivery is improved by intra-nasal rather than intra-peritoneal luciferin administration. - Buckley,SM; Howe,SJ; Wong,SP; Buning,H; McIntosh,J; Baker,A; Nathwani,AC; Thrasher,A; Coutelle,C; McKay,TR; Waddington,S (Hum Gene Ther, 2008)
In vivo bioimaging of transgenic luciferase in the lung and nose is an expedient method of continually measuring expression of this marker gene after gene transduction. Standardly, its substrate, luciferin, is injected into the peritoneal cavity prior to bioimaging. Here we demonstrate that, compared with intra-peritoneal injection, intra-nasal instillation of luciferin confers approximately an order of magnitude increase in luciferase bioluminescence detection in both lung and nose. This effect was observed following administration of viral vectors based on adenovirus-5, AAV8 and gp64-pseudotyped HIV lentivirus and, to a lesser extent, after non-viral PEI DNA delivery. Detection increased relative to the concentration of luciferin however a standard concentration of 15 mg/ml was well beyond the saturation point. Compared with intra-peritoneal injection, intra-nasal instillation yields around a ten-fold increase in sensitivity with an approximate thirty-fold reduction in the luciferin usage when bioimaging in the nasal and pulmonary airways of mice.